2019
DOI: 10.5672/apunts.2014-0983.cat.(2019/2).136.05
|View full text |Cite
|
Sign up to set email alerts
|

Resultats, dificultats i millores del model de responsabilitat personal i social

Abstract: This study aims to ascertain the effects, determinants and proposals for improvement of the Model of Personal and Social Responsibility (MPSR) from the vantage point of teachers who have implemented this model. After receiving a training program, sixteen physical education teachers used the MPSR with 315 primary and secondary school students. Group interviews were held with the participating teachers. The teachers believed that their students' attitudes and values improved, as had their own skills. The type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Regarding the will to continue implementation of the model-based program later, a positive predisposition is shown, conforming with the results of Sánchez-Alcaraz et al [45], although this research indicates that it 'works with everyone [students]' while Kallusky [51] and Martinek, Schilling and Hellison [52] noted that the model was more effective in those more disruptive students. In this sense, in connection with the perception of the effects on the students, this research has highlighted 'the need for the involvement of several highly influential groups such as the family ( .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding the will to continue implementation of the model-based program later, a positive predisposition is shown, conforming with the results of Sánchez-Alcaraz et al [45], although this research indicates that it 'works with everyone [students]' while Kallusky [51] and Martinek, Schilling and Hellison [52] noted that the model was more effective in those more disruptive students. In this sense, in connection with the perception of the effects on the students, this research has highlighted 'the need for the involvement of several highly influential groups such as the family ( .…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with research that has analyzed teachers' perception of TPSR regarding their instructional training, such as Ibaibarriaga and Tejero-González [49], we found that teachers prefer training courses that are extended over time rather than intensive courses such as those of Sánchez-Alcaraz et al [22] and Escartí et al [50], with short sessions orientated to practice; this last consideration coinciding with the conclusions of Escartí et al [41]. More specifically, the teachers involved in Sánchez-Alcaraz et al [45] did indicate that, compared to the former methodology, the TPSR could be more difficult to implement in some contexts, especially those in which there are no rules or regulation, such as body language. Teachers interviewed in this study did not make distinctions in content, affirming, in a simpler way, that this methodology 'allows them to cope better with students'.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Sport Education Model (hereon, SEM) and Teaching Personal and Social Responsibility Model (hereon, TPSR) are two examples of this changing process (Bessa et al, 2019;Sánchez-Alcaraz et al, 2019). The first one, SEM, is focused on values related to "fair play" throughout sports.…”
Section: Introductionmentioning
confidence: 99%
“…▪ Level 0: Irresponsibility ▪ Level I: Respect and self-control ▪ Level II: Participation and effort ▪ Level III: Self-direction ▪ Level IV: Leadership and caring ▪ Level V: Transfer Throughout each level, TPSR develops social values (respect, teamwork and cooperation) and personal values (effort and personal autonomy). The sequence is developed through the sessions being aware that the objectives of each level should be achieved before moving on to the next level (Hellison, 2011;Sánchez-Alcaraz et al, 2019). In the subsection Methods, a deeper description of each element is provided.…”
Section: Introductionmentioning
confidence: 99%